De Afstamming in de Landen van de Maghreb - Van Mensel, Alfons (Afrika Focus, 1990)
The modern codices which govern the personal and family law of islamic people, stay totally absorbed and influenced, by traditional Islamic law. The main issue in the parentage problem is marriage. Only within marriage, children can legally be procreated The few adaptations brought about, such as the possibility to adopt, the recognition of natural children in Tunisia, do not change the public image in many ways. Large attention is focused at the protection of the legitimate biological family-unit. This does not prevent that a very human treatment, in respect of the parentage of children, has been elaborated. Children are being placed, as much as possible, in the case of a legimitate family through techniques as there exists : recognition by men and women of children with unknown origin, the appointment by children of men and women as their father and mother, ... Belgian judges, confronted with the application of Islamic law, are showing signs of shortsightedness. Too frequently, Islamic law is put aside in favor of international public order. KEY WORDS : adoption, islam, islamic law